Gender Gap in Intergenerational Educational Persistence: Can Compulsory Schooling Reduce It? - Merve Demirel; Cagla Okten (Institute of Labor Economics (IZA), 2020)
We analyze the impact of an increase in compulsory schooling policy on the gender gap in intergenerational educational persistence using the Turkish Adult Education Survey (2012). Prior to the reform there is a gender gap in the association of parents' educational attainment with their offspring's. Daughters exhibit more intergenerational persistence than sons. We show that the education reform that increased compulsory schooling from 5 to 8 years, exposed children born after 1986 to 3 more years of schooling and reduced the effect of parental education on the completion probability of new compulsory schooling (8 years) from 30% to 1% percentage points for sons and from 49% to 11% percentage points for daughters, while the effect of parental education on post-compulsory schooling outcomes of sons and daughters decreased by 12 and 13 percentage points, respectively. The gender gap in intergenerational education transmission has decreased by 8 percentage points in the completion of new compulsory schooling level but remains unchanged at the post-compulsory schooling level after the reform.
Keywords: I20; I24; J16; J62; 330; intergenerational education transmission; gender equality; compulsory schooling